Novel beaded polymers from telechelic methacrylic ether esters - Pujari, N. S.; Trivedi, J.; Ingavle, Ganesh C.; Ponrathnam, S. (Reactive & Functional Polymers, 2006)
A series of telechelic dimethacrylic ether-esters (MEE) were prepared by solventless reaction of alpha,omega-dihydroxy poly(oxytetramethylene) (polytetrahydrofuran, PTHF) with phthalic anhydride and glycidyl methacrylate (GMA). MEE was polymerized with GMA as well as GMA-ethylene dimethacrylate (EGDM) to form porous beads. The terpolymer beads were observed using optical microscopy and SEM and characterized for internal pore volume, equilibrium volume-swelling ratio and dimethyl formamide and aqueous buffer regain. The morphology of the beads was dictated by the mole fraction and molecular weight of MEE in the feed. Porosity was found to increase with increase in molecular weight of MEE. Thus, porosity as high as 49%, 50% and 55% was observed with MEE of molecular weights 1580, 2580 and 3480, respectively. At a specific terpolymerization feed ratio of monomers, the terpolymers formed transform from gel like structure into a macroporous one, with increase in molecular weight of MEE. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: ether-ester dimethacrylates; macroporous; Pore size distribution; porosity; telechelics

Poly(High Internal Phase Emulsion) of 2-EHA, 2-EHMA and EGDA with naturally occurring phenolic compounds", paper presented at international conference on ?polymers for advanced technology - Ingavle, Ganesh C.; Shaikh, A. A.; Bhongale, Sunil Sitaram; Scaria, S.; Chavan, Nayaku; Qureshi, Mohammed; Ponrathnam, Surendra (Polymers for Advanced Technology, 2006)

Immobilization of mushroom polyphenol oxidase on poly(allyl glycidyl ether-co-ethylene glycol dimethacrylate) macroporous beaded copolymers - Vaidya, Bhalchandra K.; Karale, Abhijeet J.; Suthar, Hitesh K.; Ingavle, Ganesh C.; Pathak, Tara Sankar; Ponrathnam, S.; Nene, Sanjay (Reactive & Functional Polymers, 2007)
Functional, macroporous, beaded copolymers containing epoxy groups were synthesized for immobilization of polyphenol oxidase (PPO) from edible mushroom (Agaricus bisporus). The effect of incorporation of two different sets of monomers such as glycidyl methacrylate (GMA) and allyl glycidyl ether (AGE) and the effect of cross-linking agent ethylene glycol dimethacrylate (EGDM) with varying cross-link densities on binding and expression of mushroom PPO activity were studied. The effect of porogen viz. cyclohexanol and hexanol on PPO immobilization was studied. AGE copolymers with hexanol as a porogen were found to give higher binding and expression of PPO activity than GE polymers. Crosslinking of amino groups of enzyme with 5% glutaraldehyde for 6 h gave a stable binding of PPO on AGE-75(Hex) polymer with storage half-life of approximately 25 days. Under optimum conditions, AGE-75(Hex) polymer gave 70.3% of activity yield while percent retention of PPO activity was found to be 83.5%. Immobilized PPO showed a broader pH, higher temperature and excellent storage stability. (c) 2007 Elsevier Ltd. All rights reserved.
Keywords: cross-linking agent; Enzyme immobilization; Epoxy-activated support; mushroom PPO

Low density porous carrier based conceptual drug delivery system - Sher, Praveen; Ingavle, Ganesh C.; Ponrathnam, Surendra; Pawar, Atmaram P. (Microporous and Mesoporous Materials, 2007)
Chronotherapy, a new approach for treating pathological conditions, is based on circadian rhythm. Present work conceptualizes a specific technology, based on combining floating and pulsatile principles to develop drug delivery system, intended for chronotherapy in arthritis. This approach was achieved by using low density microporous polypropylene, Accurel MP 1000 (R), as a multiparticulate carrier along with drug of choice ibuprofen. Carrier amount and solvent volume was kept invariant in designing this simple system by adsorbing drug via melting or solvent evaporation using different carrier: drug ratios. In solvent evaporation, methanol (M) and dichloromethane (DCM) were used. Drug loaded multiparticulate system was subjected to various characterization and evaluation parameters showing influence of adsorption process. Drug release study was performed in acidic environment using pH 1.2 HCl IP medium for 6 h to mimic gastric condition for evaluating gastroretention followed by basic environment using appropriate medium as phosphate buffer pH 7.2 IP for 3 h resembling transit. The release pattern showed influence of drug adsorption methods characterized by ever changing pore geometry with total release ranges in acidic medium as 10.7-27.6% and final release as 55.6-88.6%. Present drug delivery system devoid of any additives/excipients influencing drug release show distinct behaviour from other approaches/technologies in chronotherapy by (a) observing desired low drug release (11%) in acidic medium (b) overcoming the limitations of process variables caused by multiple formulation steps (c) reducing time consumption due to single step process (d) can be extended to controlled release also. (C) 2007 Elsevier Inc. All rights reserved.
Keywords: chronotherapy; floating pulsatile drug delivery; low density porous carrier; melt adsorption; solvent polarity

Low density porous carrier - drug adsorption and release study by response surface methodology using different solvents - Sher, Praveen; Ingavle, Ganesh C.; Ponrathnam, Surendra; Pawar, Atmaram P. (International Journal of Pharmaceutics, 2007)
Low density porous carriers are widely used in the pharmaceutical applications. Response surface methodology, using 3 2 factorial design was used to study drug adsorption on and its release patterns from microporous polypropylene (Accurel MP 1000((R))) in the absence of additives. Ibuprofen, as model drug, was adsorbed on the polymer by solvent evaporation using two organic solvents methanol (M) and dichloromethane (DCM). The amount of carrier (100 mg) and its particle size range (250-350 mu m) were kept invariant while solvent volume (X-1) and drug amount (X-2) were taken as variables. Drug adsorption pattern depended on the type and amount of solvent used. DSC, XRD, FTIR and TGA, predict crystalline nature and physical form of adsorption. SEM showed the penetration and adsorption of the drug in and on the microporous polymer. Accurel NIP 1000((R)) had a pore volume of 1.992 g/cm(3) and surface area of 55.9855 m(2)/g as detected by mercury porosimetery. On drug adsorption, pore volume ranged from 0.413 to 1.198 g/cm(3) for methanol and 0.280-0.759 g/cm(3) for DCM. Similarly surface area was in the range 38.445-25.497 m(2)/g for methanol and 18.710-32.528 m(2)/g for DCM. The drug release was investigated in phosphate buffer pH 7.2. All batches showed excellent in vitro floating property. Drug release was partial with recovery to complete dependent on type and volume of solvent. R 2 values relating to bulk density, pore volume, surface area and drug release at 60, 120 and 180 min were estimated. Effect of solvent properties shows a positive influence on drug adsorption and release. Release profiles of some batches could be considered as gastroretentive drug delivery system. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: 3(2) factorial design; carrier; microporous polymer; Response surface methodology; solvent evaporation

Macroporous beads for lipase immobilization: kinetic resolution of a racemic drug intermediate - Bhushan, Indu; Parshad, Rajinder; Qazi, G. N.; Ingavle, Ganesh C.; Jamalpure, Trupti M.; Rajan, C. R.; Ponrathnam, Surendra; Gupta, V. K. (Journal of Bioactive and Compatible Polymers, 2007)
{Lipase isolated from Arthrobacter sp. (RRLJ-1, MTCC No. 5125, named ABL), is effective in resolving a wide range of racemic drug intermediates. In this study, ABL was immobilized on a series of synthetic macroporous epoxy copolymers beads with varying pore sizes, surface area and hydrophobicity. Poly(glycidyl methacrylate-co-ethylene dimethacrylate) beads, with 75% crosslink density and 10% of epoxy groups modified with dibutyl amine [
Keywords: auxin pulse; coco-peat; grape; micropropagation; plantlet survival

Removal of AS(III) and AS (V) from contaminated water sources by sorption onto novel pei-attached poly(hipe) beads", paper presented at international conference on ?role of analytical chemistry in nuclear technology? - Ingavle, Ganesh C.; Tayal, Rajeev; Shaikh, Wasif Abdul Lateef; Chaudhari, Sanjeev; Chavan, Nayaku; Rajan, Chelanattukizhakkemadath Raman; Ponrathnam, Surendra (Role of Analytical Chemistry in Nuclear Technology, 2007)

Immobilization of Candida rugosa lipase on poly(allyl glycidyl ether-co-thylene glycol dimethacrylate) macroporous polymer particles - Vaidya, Bhalchandra K.; Ingavle, Ganesh C.; Ponrathnam, S.; Kulkarni, B. D.; Nene, Sanjay N. (Bioresource Technology, 2008)
Macroporous polymer particles containing surface epoxy groups were synthesized for immobilization of Candida rugosa lipase (CRL). The effect of incorporation of two different sets of monomers [allyl glycidyl ether (AGE) and glycidyl methacrylate (GMA)] and the effect of crosslinking density on immobilization of lipase were studied. AGE-co-EGDM polymers gave higher binding and expression of lipase than GMA-co-EGDM polymers. Optimization of immobilization parameters was done with respect to immobilization time and enzyme loading. Amongst AGE-co-EGDM polymer series, AGE-150 polymer found to give maximum lipase activity yield and therefore evaluated for temperature, pH and storage stability. Under optimum conditions, AGE-150 polymer gave 78.40% of activity yield. Immobilized lipase on AGE-150 showed a broader pH, higher temperature and excellent storage stability. (C) 2007 Published by Elsevier Ltd.
Keywords: Candida rugosa lipase; Enzyme immobilization; Epoxy-activated support

Lipase enzyme immobilization on synthetic beaded macroporous copolymers for kinetic resolution of chiral drugs intermediates - Bhushan, Indu; Parshad, Rajinder; Qazi, Gulam Nabi; Ingavle, Ganesh C.; Rajan, C. R.; Ponrathnam, Surendera; Gupta, Vijay Kumar (Process Biochemistry, 2008)
Lipase isolated from Arthrobacter sp. (bacterial strain, MTCC No. 5125) at RRL Jammu, being used for various process development. Arthrobacter sp. lipase (ABL) now has been immobilized on synthetic polymers and reused many a times. In this investigation number of various synthetic macroporous alkylated glycidyl epoxy copolymers with varying hydrophobicity, pore volume and surface area were prepared and used for this study. Among all the polymers prepared and used only two epoxy polymers GMA-EGDM 75-20(I) and GMA-EGDM 75-30(I) with particle size in the range of 150-450 nm, epoxy groups 80 and 70%, tertiary amino groups 20 and 30% was found suitable for immobilization of lipase (ABL). Dibutyl amine (DBA) incorporation created an internal pore radii 20-50 nm and hydrophobic microenvironment in both the polymers for binding the enzyme, which led to improvement in stability and enatioselectivity in racemic resolution process especially by binding to one of the isomers. The optimal ABL binding capacity of polymer GMA-EGDM 75-20(I) was 60 units, 34 mg protein and GMA-EGDM 75-30(l) was 36 units, 21 mg protein/g polymer. The immobilized lipase matrices displayed enhanced pH, thermal, organic solvent and long-term storage stability. Both the immobilized enzyme matrices were tested firstly for the hydrolysis of triglycerides using tributyrin as substrate. After testing, both the matrices were reused for racemic resolution of ethyl-3-hydroxy-3-phenyl propanoate (fluoxetine intermediate, an antidepressant drug) and racemic chiral auxiliary, acetyl-1-phenyl ethanol (intermediate of many chiral drugs) for 15 cycles. These immobilized lipase matrices have shown very high stability on recycling, high-enantioselectivity, high conversion and faster recovery of product compare to free enzyme, therefore these matrices may find use in kinetic resolution process developments. (C) 2007 Elsevier Ltd. All rights reserved.
Keywords: 1-phenyl ethanol and enantioselectivity; chiral resolution; enantiomeric excess (ee); ethyl-3-hydroxy-3-phenyl propanoate; Immobilization; Lipase

Modulation and optimization of drug release from uncoated low density porous carrier based delivery system - Sher, Praveen; Ingavle, Ganesh C.; Ponrathnam, Surendra; Poddar, Pankaj; Pawar, Atmaram P. (AAPS Pharmscitech, 2009)
The purpose of this research work was to explore an application of uncoated porous drug carrier prepared by single-step drug adsorption for a delivery system based on integration of floating and pulsatile principles intended for chronotherapy. This objective was achieved by utilizing 3(2) factorial design, solvent volume (X (1)) and drug amount (X (2)) as selected variables, for drug adsorption using solvents, methanol, and dichloromethane (DCM), of varying polarity. Nitrogen adsorption (N(2)), scanning electron microscopy of cross-sections, and atomic force microscopy were done to study adsorption patterns and their effect on release pattern. Drug release study was customized by performing for 6 h in acidic environment to mimic gastroretention followed by basic environment akin to transit phase. Correlation between porous data from mercury and N(2) adsorption was probably studied for the first time. Observed regression analysis values for pore volume, surface area, and drug release indicated the influence of selected variables. Total release range in acidic medium was 12.77-24.57% for methanol, 8.79-15.26% for DCM, and final release of 69.45-92.23% for methanol, and 60.16-99.99% for DCM influenced by varying internal geometries was observed. Present form of drug delivery system devoid of any additives/excipients influencing drug release shows distinct behavior from other approaches/technologies in chronotherapy by (a) observing desired low drug release (8%) in acidic medium, (b) overcoming the limitations of process variables caused by multiple formulation steps and different characteristic polymers, (c) reducing time consumption due to single step process, and (d) extending as controlled/extended release.
Keywords: chronotherapy; floating pulsatile drug delivery system; low density porous carrier; pore data; solvent polarity

Novel/conceptual floating pulsatile system using high internal phase emulsion based porous material intended for chronotherapy - Sher, Praveen; Ingavle, Ganesh C.; Ponrathnam, Surendra; Benson, James R.; Li, Nai-Hong; Pawar, Atmaram P. (AAPS Pharmscitech, 2009)
The aim of the present study was to design a novel/conceptual delivery system using ibuprofen, anticipated for chronotherapy in arthritis with porous material to overcome the formulation limits (multiple steps, polymers, excipients) and to optimize drug loading for a desired release profile suitable for in vitro investigations. The objective of this delivery system lies in the availability of maximum drug amount for absorption in the wee hours as recommended. Drug loading using 3(2) factorial design on porous carrier, synthesized by high internal phase emulsion technique using styrene and divinylbenzene, was done via solvent evaporation using methanol and dichloromethane. The system was evaluated in vitro for drug loading, encapsulation efficiency, and surface characterization by scanning electron, atomic force microscopy, and customized drug release study. This study examined critical parameters such as solvent volume, drug amount, and solvent polarity on investigations related to drug adsorption and release mostly favoring low-polarity solvent dichloromethane. Overall release in all batches ranged 0.98-52% in acidic medium and 71-94% in basic medium. These results exhibit uniqueness in achieving the least drug release of 0.98%, an ideal one, without using any release modifiers, making it distinct from other approaches/technologies for time and controlled release and for chronotherapy.
Keywords: chronotherapy; floating pulsatile drug delivery system; high internal phase emulsion; ibuprofen; multiparticulate porous carriers

Adsorption induced enzyme denaturation: the role of polymer hydrophobicity in adsorption and denaturation of alpha-chymotrypsin on allyl glycidyl ether (AGE)-ethylene glycol dimethacrylate (EGDM) copolymers - Lahari, Challa; Jasti, Lakshmi Swarnalatha; Fadnavis, Nitin W.; Sontakke, Kalpana; Ingavle, Ganesh C.; Deokar, Sarika Babasaheb; Ponrathnam, Surendra (Langmuir, 2010)
Effects of changes in hydrophobicity of polymeric support oil structure and activity of alpha-chymotrypsin (E.C.3.4.21.1) have been studied with copolymers of allyl glycidyl ether (AGE) and ethylene glycol dimethacrylate (EGDM) with increasing molar ratio of EGDM to AGE (cross-link density 0.05 to 1.5). The enzyme is readily adsorbed front aqueous buffer at room temperature following Langmuir adsorption isotherms in unexpectedly large amounts (25% w/w). Relative hydrophobicity of the copolymers has been assessed by studying adsorption of naphthalene and Fmoc-methionine by the series of copolymers from aqueous solutions. Polymer hydrophobicity appears to increase linearly oil increasing cross-link density from 0.05 to 0.25. Further increase in cross-link density Causes a decrease in naphthalene binding but has little effect on binding of Fmoc-Met. Binding of alpha-chymotrypsin to these copolymers follow the trend for Fmoc-methionine binding, rather than naphthalene binding, indicating involvement of polar interactions along with hydrophobic interactions during binding of protein to the polymer. The adsorbed enzyme undergoes extensive denaturation (ca. 80%) with loss of both tertiary and secondary structure on contact with the copolymers as revealed by fluorescence, CID and Raman spectra of the adsorbed protein. Comparison of enzyme adsorption behavior with Eupergit C, macroporous Amberlite XAD-2, and XAD-7 Suggests that polar interactions of the EGDM ester functional groups with the protein play a significant role in enzyme denaturation.

Poly(allyl glycidyl ether-co-ethylene glycol dimethacrylate) copolymer beads as support for covalent immobilization of L-aminoacylase - Vaidya, Bhalchandra K.; Ingavle, Ganesh C.; Ponrathnam, S.; Nene, Sanjay N. (Reactive & Functional Polymers, 2012)
Porous epoxy-activated copolymer beads were synthesized as support for the covalent immobilization of Aspergillus melleus L-aminoacylase. Here, a series of copolymer bead were synthesized using either glycidyl methacrylate (GMA) or ally] glycidyl ether (AGE) as monomer units and ethylene glycol dimethacrylate (EGDM) as cross-linking agent. The effect of monomer used and the effect of amount of cross-linking agent on covalent immobilization of aminoacylase were studied. Furthermore, the effect of porogen on immobilization of aminoacylase was also evaluated. AGE-co-EGDM copolymer beads gave higher binding of aminoacylase than GMA-co-EGDM copolymer beads. AGE-co-EGDM copolymer beads synthesized with lauryl alcohol as porogen and having 150% cross-linked density (i.e. AGE-(L)-150) gave maximum enzyme binding. Under optimum conditions, AGE-(L)-150 copolymer beads gave about 130 U/g of aminoacylase activity which corresponds to 72.24% of activity yield. Immobilized aminoacylase showed a broader pH, higher temperature and extended storage stability. (C) 2012 Elsevier Ltd. All rights reserved.
Keywords: Enzyme immobilization; Epoxy-activated support; L-Aminoacylase